Evaluating Preventive Strategies for Bronchopulmonary Dysplasia in Preterm Neonates: A Systematic Review: Preventive Strategies for BPD in Preterm Neonates - Gul, Madiha; Alam, Sadaf; Durani, Aisha; Raziq, Mahnoor; Javed, Hafiz Muhammad Nouman; Ullah, Hameed (Pakistan Journal of Health Sciences, 2025)
Bronchopulmonary dysplasia (BPD) remains a major complication in preterm neonates, affecting long-term respiratory health and quality of life. Despite advances in neonatal care, identifying consistently effective preventive strategies remains a clinical challenge. Objectives: To evaluate recent evidence on interventions used to prevent BPD in preterm neonates, focusing on identifying effective strategies and addressing current research gaps. Methods: A structured literature search was conducted using PubMed, Embase, Cochrane Library, and Web of Science for studies published between January 2016 and March 2025. Eligible studies included randomized controlled trials, prospective cohorts, and observational studies evaluating interventions in neonates born before 32 weeks of gestation or weighing under 1500 grams. Screening and data extraction were performed independently. Methodological quality was assessed using standard tools. Results: Eighteen studies met the inclusion criteria. Interventions evaluated included non-invasive ventilation, minimally invasive surfactant therapy (MIST), pharmacologic agents (melatonin, corticosteroids, intra-tracheal budesonide), and nutritional supplementation (vitamins A and D, fatty acids). MIST, melatonin, budesonide with surfactant, and early vitamin D supplementation consistently reduced BPD incidence. In contrast, vitamin A, maternal DHA supplementation, and systemic hydrocortisone showed limited or inconsistent benefit. Conclusions: Several interventions, particularly MIST, budesonide with surfactant, melatonin, and vitamin D, appear effective in preventing BPD in preterm infants. However, inconsistencies in outcomes from other therapies underscore the need for further high-quality trials to guide clinical practice.